(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
In this article, the optical and isogonal properties of conic sections - parabola, hyperbola, and ellipse - are analyzed using examples of their practical applications in astronomical telescope systems (Newtonian, Cassegrain, Gregorian). Based on the laws of analytical geometry, the focusing processes of light rays are proven, and practical metric problems related to the design of telescope mirrors are presented with solutions.